Dog bites to the upper extremity in children. (17th June 2015) - Speirs, Joshua; Showery, James; Abdou, Marwa; Pirela‐Cruz, Miguel A; Abdelgawad, Amr A
Abstract : Aim: Dog bites are common injuries in children. A large percentage of these dog bites affect the upper extremity. There is little information describing the results of treatment of upper extremity injuries in children. Methods: We retrospectively reviewed the medical records for all children less than 19 years old who presented to the emergency department in our level one trauma centre because of dog bites from 2005 to 2011. Results: During the study period, there were 254 paediatric emergency department visits for animal bites, among these there were 118 dog bites, two were excluded because of inadequate documentation leaving 116 patients; 26 of them (22.4%) had bites to the upper extremity. Among the 26 children with dog bites to the upper extremity, 6 (23.1%) were admitted to the hospital for surgery (four patients) or parenteral antibiotics (two patients). Among the four surgeries, two were for extensive laceration and two were for abscess debridement. Of the 41 who presented with bites to the lower extremities, none were admitted to the hospital ( P = 0.002). Compared with those who presented the same day they were injured, the relative risk of hospitalization or surgery in patients who presented 1 and 2 days after their injury was 3.5 and 7.0, respectively. Conclusion: Dog bites at the upper extremity are more prone to require surgical intervention and develop infection than those at the lower extremity, and delayed presentation of these injuries is associated with higher incidence of developing infection.